Management for Patients with De Novo or Recurrent Tumors in the Residual Kidney after Surgery for Nonfamilial Bilateral Renal Cell Carcinoma - Noboru Hara; Tsutomu Nishiyama; Norihiko Yoshimura; Satoshi Takaki; Kyoichiro Yamakado; Yasuo Kitamura; Kazuya Suzuki; Kota Takahashi (Advances in Urology)
The tumor de novo in the residual kidney after surgery for nonfamilial bilateral renal cell carcinoma (RCC) is problematic. We reviewed 5 patients who experienced such a situation. Three patients had had metachronous bilateral RCC, treated with radical nephrectomy in one kidney and nephron-sparing surgery (NSS) in the other. Two patients had had synchronous disease; one patient had received radical nephrectomy and NSS, and the other bilateral NSS. The 5 patients had another solid mass/de novo tumor in the residual kidney 16–88 (mean 46.8) months after surgery. For the tumor de novo in earlier years (1992–1999), one patient underwent surgery and hemodialysis, and the other selected a conservative observation. In recent years (2000–2007), one patient was conservatively observed; the remaining 2 received computerized-tomography-guided radiofrequency ablation, and the local tumors were well controlled postoperatively for 20 and 12 months with their renal function unimpaired. Ablative techniques can potentially strike a balance between oncological and nephrological outcomes in patients with sporadic multiple RCC, successful management of which was difficult previously.